2020
DOI: 10.1136/annrheumdis-2020-eular.6093
|View full text |Cite
|
Sign up to set email alerts
|

Sat0092 cardiovascular Risk Assessment in Patients With Autoimmune Rheumatic Diseases: An Italian Rheumatologists’ Survey

Abstract: Background:Cardiovascular (CV) disease is the leading cause of morbidity and mortality in patients with inflammatory arthritis. The growing attention to the CV risk characterizing patients with autoimmune inflammatory disease led EULAR to provide recommendations on CV risk management (1). To date, there are no data on the adherence to EULAR recommendation among Italian rheumatologists.Objectives:Our objective was to measure the level of awareness and the attitude to manage CV risk.Methods:Italian rheumatologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Despite the wide consensus that ARDs are associated with increased CVR ( 44 , 45 ), and recent initiatives to drive collaborations between Rheumatology and Cardiology to improve the risk stratification of ARD patients ( 46 ), there is a paucity of data regarding the performance of various CVR assessment tools in ARD cohorts of all ages. A recent survey of Italian rheumatologists revealed that 67.2% rheumatologists routinely assess the CVR in their patients, while only 18.6% declared that they were managing the patients' CVR themselves, and 50% refer them to other specialties and 23.4% to the general practitioners ( 47 ).…”
Section: What Cvr Scores Can Be Used In Younger Patients With Ards?mentioning
confidence: 99%
“…Despite the wide consensus that ARDs are associated with increased CVR ( 44 , 45 ), and recent initiatives to drive collaborations between Rheumatology and Cardiology to improve the risk stratification of ARD patients ( 46 ), there is a paucity of data regarding the performance of various CVR assessment tools in ARD cohorts of all ages. A recent survey of Italian rheumatologists revealed that 67.2% rheumatologists routinely assess the CVR in their patients, while only 18.6% declared that they were managing the patients' CVR themselves, and 50% refer them to other specialties and 23.4% to the general practitioners ( 47 ).…”
Section: What Cvr Scores Can Be Used In Younger Patients With Ards?mentioning
confidence: 99%